Lifestyle Practices and Prevalence of obesity in a Community Within a university - Moy, Foong Ming; Atiya, A.S. (Faculty of Medicine, University of Malaya, 2005)
Malaysia has undergone rapid pace of industrialization and urbanization in recent decades and this has brought about imminent changes in the lifestyle of Malaysians. This is a cross-sectional study which attempts to examine the lifestyle practices and the prevalence of obesity of a group of security guards and their spouses of the University of Malaya, Kuala Lumpur. Data collection was conducted by both the methods of face-to-face interview and self-administered questionnaire. The respondents were surveyed on lifestyle practices such as smoking habits, exercise and eating pattern. Anthropometric measurement such as weight and height were also taken to establish the extend of obesity by using Body Mass Index (BMI). This study reveals that the community did have some unhealthy Lifestyle practices such as smoking (27.7%; 95%CI 20.2%, 36.2%), low prevalence of adequate exercise (13.8%;95%CI 8.4%, 21.0%); high prevalence of overweight and obesity (64%; 95%CI 55.1%, 72.3%); and high prevalence of co-morbidities such as diabetes mellitus and cardiovascular diseases. In conclusion, the community is considered to be a vulnerable and high-risk group for morbidity and mortality with the above predisposed risk factors.